2009
DOI: 10.1136/bmj.b2243
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cost effectiveness of screening Danish men aged 65 for abdominal aortic aneurysm

Abstract: Objective To assess the cost effectiveness of screening men aged 65 for abdominal aortic aneurysm. Design Cost effectiveness analysis based on a probabilistic, enhanced economic decision analytical model from screening to death. Population and setting Hypothetical population of men aged 65 invited (or not invited) for ultrasound screening in the Danish healthcare system. Data sources Published results from randomised trials and observational epidemiological studies retrieved from electronic bibliographic datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 23 publications
0
64
0
Order By: Relevance
“…61 These have all concluded that screening is acceptably cost-effective, with the exception of a study using data from Denmark and other sources, which concluded that screening did not seem to be cost-effective. 62 A recent modelling study, again using Danish data, contradicts that previous conclusion, suggesting that screening men at age 65 years is highly cost-effective compared with no screening and, additionally, that rescreening after 5 years may be a cost-effective extension to the programme. 63 However, no models of cost-effectiveness of AAA screening have been published that have specific relevance to NAAASP, other than those already cited relating to and derived from the MASS study, which is the largest randomised trial of AAA screening and contributes most to the international evidence.…”
Section: Introductionmentioning
confidence: 41%
“…61 These have all concluded that screening is acceptably cost-effective, with the exception of a study using data from Denmark and other sources, which concluded that screening did not seem to be cost-effective. 62 A recent modelling study, again using Danish data, contradicts that previous conclusion, suggesting that screening men at age 65 years is highly cost-effective compared with no screening and, additionally, that rescreening after 5 years may be a cost-effective extension to the programme. 63 However, no models of cost-effectiveness of AAA screening have been published that have specific relevance to NAAASP, other than those already cited relating to and derived from the MASS study, which is the largest randomised trial of AAA screening and contributes most to the international evidence.…”
Section: Introductionmentioning
confidence: 41%
“…In the long-term run screening was found to be even more cost effective, at a probability above 0.97 for a willingness to pay threshold of Euro 5000 (Lindholt et al, 2010). In contrast, the cost effectiveness of screening Danish men aged 65 for AAA was rejected by Ehlers et al, 2009a. They developed a decision tree and Markov model to simulate the short-term and long-term effects of screening for AAA.…”
Section: Cost Effectiveness Of Screening For Aaamentioning
confidence: 99%
“…This latter approach will benefit from a higher prevalence of AAA and thus show a better cost effectiveness (Ehlers et al 2009b). Ehlers et al, 2009a emphasized that ultrasonography may be cheap on a per person basis, but screening is not just a test but a program. If screening is to be effective then overall administration of the program, operational planning, a communication strategy, a quality assurance system, and more are needed.…”
Section: Cost Effectiveness Of Screening For Aaamentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of the AAA reflects the magnitude of the degenerative process of the wall and this is a marker of rupture. Therefore, the need for additional strategies to refine cost effectiveness of screening programs is currently advocated [7]. AAA is a multifactorial disease.…”
Section: Introductionmentioning
confidence: 99%